2002
DOI: 10.1034/j.1600-0765.2002.01611.x
|View full text |Cite
|
Sign up to set email alerts
|

Hard tissue formation on dentin surfaces applied with recombinant human bone morphogenetic protein‐2 in the connective tissue of the palate

Abstract: The purpose of this study was to evaluate whether hard tissue might be formed on dentin surfaces applied with recombinant human bone morphogenetic protein-2 (rhBMP-2) in palatal connective tissue. Fifty-eight dentin blocks were prepared from rat roots, demineralized with 24% EDTA (pH 7.0), applied with 0, 50 and 100 microgram/ml rhBMP-2, and labeled as groups 0, 50 and 100. The dentin blocks were then transplanted into palatal connective tissue of rats, and specimens were prepared at two and four weeks after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…This finding demonstrates that the cleft palate connective tissue cells respond to external BMP-2 becoming bone forming cells, thus allowing us to suggest that in an in vivo cleft palate model extra bone would be produced from these cells if conveniently induced. Interestingly, the BMP-2 induction of bone occurred in the tgf-␤ 3 null mice palate, similar to the observed in wild type rodents [31,32], indicate that the alteration of the tgf-␤ 3 gene does not modify this tissue response to BMP-2. No differences were observed between BMP-2 treated and untreated cultures at either 24 h or 3 weeks.…”
Section: Discussionsupporting
confidence: 75%
“…This finding demonstrates that the cleft palate connective tissue cells respond to external BMP-2 becoming bone forming cells, thus allowing us to suggest that in an in vivo cleft palate model extra bone would be produced from these cells if conveniently induced. Interestingly, the BMP-2 induction of bone occurred in the tgf-␤ 3 null mice palate, similar to the observed in wild type rodents [31,32], indicate that the alteration of the tgf-␤ 3 gene does not modify this tissue response to BMP-2. No differences were observed between BMP-2 treated and untreated cultures at either 24 h or 3 weeks.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, cementum would regenerate on the root‐planed surfaces. Second, mesenchymal progenitor cells originating from gingival connective tissues differentiate into cementoblasts on rhBMP‐2 implantation and would regenerate cementum on the root‐planed surface 38–40 …”
Section: Discussionmentioning
confidence: 99%
“…While studies involving the use of exogenously administered recombinant BMP-2 and BMP-7 to induce bone regeneration have generally been promising in lower animals 3,4,5 , human studies have demonstrated a large variation in response to recombinant BMP 6 . Additionally, the short in vivo half-life of rBMPs 7 , coupled with the ability of pharmacologic doses of BMPs to stimulate osteoclast production 8 , may limit the usefulness of recombinant BMPs in the clinical setting 9 .…”
Section: Introductionmentioning
confidence: 99%